Effect of Floating Metallic Particles in Pre-Breakdown and Breakdown Characteristics of Oil Transformer under DC Voltage - I. Made Yulistya Negara; Daniar Fahmi; Dimas Anton Asfani; I. G. N. Satriyadi Hernanda; Mochammad Wahyudi; Muhammad Novis Ibrahim (Energies, 2021)
Contaminants in transformer oil insulation can float when meeting several conditions. Then, the presence of floating contaminants affects the electrical characteristics of oil insulation. Therefore, the pre-breakdown (corona) and breakdown characteristics due to metallic floating particles in transformer oil insulation would be investigated. This test used DC high voltage stress. A 56 Ω resistor was connected to the oscilloscope to detect the corona currents. The camera was used to capture the images of corona light emission. In addition, the electric field between the electrode and particles was simulated. The variables were the particle size, including its shape, and the distance between the particles and the grounded electrode. The experimental results show that the average value of corona inception and breakdown was inversely proportional to the size of floating particles. The peak value of corona current was directly proportional to the particle size. The lowest breakdown voltage was found when the particle was close to the electrode, but they were not in contact.